The house of death - Tremayne, Peter (Severn House, an imprint of Canongate Books Ltd, 2021)
"Ireland. AD 672. The Feast of Beltaine is approaching and the seven senior princes of the kingdom of Muman are gathering at Cashel to discuss King Colgu's policies. Just days before the council meets, Brother Conchobhar, the keeper of the sacred sword, is found murdered. Sister Fidelma and her brother Colgú fear that the killer had been trying to steal the sword that symbolises the King's authority to rule. And as rumours begin to spread of an attempt to overthrow Colgú, news reaches Cashel that a plague ship has landed at a nearby port, bringing the deadly pestilence to its shores. Amid fear and panic, Fidelma, Eadulf and Enda must work together to catch a killer as the death toll starts to mount ."--Amazon.